Building capabilities to catch up with the biotechnological paradigm. Evidence from Argentina, Brazil and Chile agro-food systems - Gutman, Graciela Elena (2012)
Latin American countries have been historically characterised by production structures highly reliant on natural resources. The recent diffusion of modern biotechnologies has reinforced this specialisation pattern. The cases of Argentina, Brazil and Chile show that, with different rates, scopes and directions, important advances have been made in the adoption of biotechnological products and processes associated with the specificities of their natural resource endowment, their industrial structure, their science and technology infrastructure, and the institutional and public policy context. This article discusses the opportunities these new technologies offer for changing theabsolute (or comparative) advantages in the agro-food systems of those countries.